MANYAKOK CERIA SEBAGAI BENTUK PEMODERNAN TARI TRADISIONAL “MANYAKOK” KEMBALI KE KUANSING KABUPATEN SINGINGI RIAU - Idun Ariastuti; Risnawati Risnawati; Yarlis Yarlis (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
ABSTRACT Research and discussion that has been carried out in the first year said that the researchers and artists or the community supporting the dance Manyakokhave agreed to modernize it by developing the traditional danceManyakok, without losing the values contained in it in accordance to its aimto be a tourist performing art. In the second stage, the development produces a new dance compositionManyakok and returned to the supporting community through aPacuJalur tourism program. To achieve the objectives of this study, the method used is qualitative and R & D; it is also possible to use quantitative methods using a scientific approach, namely observation, literary study, field studies, modernization / development and marketing (case studies). Besides, to find out the effectiveness of the new model / form of dance composition, it needs to be tested. The test was conducted in the form of a pre-performance held on Friday, August 3, 2018 at 20.30 WIB, at the Adam ISI Huriah Building, Padangpanjang. After the pre-performance, it is followed by an open discussion. The result can be concluded that the new form of Manyakok dance composition was agreed to be entitled” Manyakok Ceria” dance. Alhamdulillah the results were very satisfying, even previously, it is planned to appear on the nightly arts event.After being shown at the pre-show, the observers from Pangean including the Regent plan to perform it at the PacuJalur. On Wednesday 29 August 2018, a new form of Manyakok dance compositions (Manyakok Ceria dance) is returned to the supporting community through performances at opening events and arts night events on the cultural program Pacu Jalur. The activity is in accordance to the objectives of the second phase of the research, namely to restore the new product of traditional dance composition of Manyakok to the community as well as an effort to preserve the traditional dance and improve the economy of the community.